2019
DOI: 10.12669/pjms.35.1.364
|View full text |Cite
|
Sign up to set email alerts
|

Does an increased number of cesarean sections result in greater risk for mother and baby in low-risk, late preterm and term deliveries?

Abstract: Objective: To compare surgical complications and maternal and neonatal outcomes of low-risk, late preterm and term pregnant women who have had one or two previous cesarean sections (CSs) with those who have had three or more CSs. Methods: We conducted a retrospective study of 850 patients undergoing repeat CS at a tertiary level maternity hospital in Ankara, Turkey. Of those, 380 had previously undergone one or two CSs (Group-I: second or third CS) and 470 had previously undergone three or four CSs (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Parece claro que la cesárea aumenta su incidencia, pero, por el contrario, las cesáreas reiterativas no parecen aumentar este riesgo (9,10) . Además, se han propuesto otros factores de riesgo como otras cirugías uterinas previas (legrado uterino, ablación endometrial), extracción manual de placenta, técnicas de fecundación in vitro (11) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Parece claro que la cesárea aumenta su incidencia, pero, por el contrario, las cesáreas reiterativas no parecen aumentar este riesgo (9,10) . Además, se han propuesto otros factores de riesgo como otras cirugías uterinas previas (legrado uterino, ablación endometrial), extracción manual de placenta, técnicas de fecundación in vitro (11) .…”
Section: Discussionunclassified
“…El riesgo de recidiva de EESCC es bajo, entre 3 y 5% (9) . A pesar del escaso riesgo de recurrencia, las pacientes con deseo gestacional deben ser informadas de las potenciales complicaciones graves con una nueva gestación.…”
Section: Discussionunclassified
“…Some have confirmed the increase in severe complications with the increase in the number of previous cesarean sections. (14,15,17) and some have not confirmed serious morbidities (18, 19). In general, there is no accurate data on the maximum number of cesarean sections that are not associated with serious consequences for subsequent cesarean sections in a woman.…”
Section: Introductionmentioning
confidence: 99%
“…As for the baby, it may have trouble breastfeeding and may be at greater risk for breathing problems [3,20,21]. Besides, evidences showed that having a CS increases the risk of complications in a later pregnancy and in other surgeries [22,23].…”
Section: Introductionmentioning
confidence: 99%